Evaluación de la influencia de las actividades de producción acuícola (Litopenaeus Vannamei) en el cambio de uso del suelo del Humedal La Segua. - Alcívar Pinargote, Jesús Divino (2018)
The general objective of this research was to evaluate the influence of aquaculture production activities (Litopenaeus vannamei) on the change of land use of the La Segua wetland, which was carried out by means of the diagnosis of the study area, and the analysis of satellite Landsat images in the periods 2007/2016 and 2017/2018, obtained in the Ecuadorian Space Institute. Using the geographic information systems, thematic maps were made to identify the different land uses in the study site, and the exchange rate in the afore mentioned periods was calculated. As a result, it was got that the shrimp aquaculture activity land use increased between 2007 and 2016 by 19,76% and, between 2017 and 2018 by 19,70%. This concludes that aquaculture production activities have an accelerated growth in the sector, influencing the change in land use and bringing consequences such as the decrease in the body of natural water.